Patterns of altered neural synchrony in the default mode network in autism spectrum disorder revealed with magnetoencephalography (MEG): Relationship to clinical symptomatology. Issue 3 (18th December 2017) - Lajiness‐O'Neill, Renée; Brennan, Jonathan R.; Moran, John E.; Richard, Annette E.; Flores, Ana‐Mercedes; Swick, Casey; Goodcase, Ryan; Andersen, Tiffany; McFarlane, Kaitlyn; Rusiniak, Kenneth; Kovelman, Ioulia; Wagley, Neelima; et al.
Abstract : Disrupted neural synchrony may be a primary electrophysiological abnormality in autism spectrum disorders (ASD), altering communication between discrete brain regions and contributing to abnormalities in patterns of connectivity within identified neural networks. Studies exploring brain dynamics to comprehensively characterize and link connectivity to large‐scale cortical networks and clinical symptoms are lagging considerably. Patterns of neural coherence within the Default Mode Network (DMN) and Salience Network (SN) during resting state were investigated in 12 children with ASD ( M Age = 9.2) and 13 age and gender‐matched neurotypicals (NT) ( M Age = 9.3) with magnetoencephalography. Coherence between 231 brain region pairs within four frequency bands (theta (4–7 Hz), alpha, (8–12 Hz), beta (13–30 Hz), and gamma (30–80 Hz)) was calculated. Relationships between neural coherence and social functioning were examined. ASD was characterized by lower synchronization across all frequencies, reaching clinical significance in the gamma band. Lower gamma synchrony between fronto‐temporo‐parietal regions was observed, partially consistent with diminished default mode network (DMN) connectivity. Lower gamma coherence in ASD was evident in cross‐hemispheric connections between: angular with inferior/middle frontal; middle temporal with middle/inferior frontal; and within right‐hemispheric connections between angular, middle temporal, and inferior/middle frontal cortices. Lower gamma coherence between left angular and left superior frontal, right inferior/middle frontal, and right precuneus and between right angular and inferior/middle frontal cortices was related to lower social/social‐communication functioning. Results suggest a pattern of lower gamma band coherence in a subset of regions within the DMN in ASD (angular and middle temporal cortical areas) related to lower social/social‐communicative functioning. Autism Res 2018, 11: 434–449 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Communication between different areas of the brain was observed in children with ASD and neurotypical children while awake, but not working on a task. Magnetoencephalography was used to measure tiny magnetic fields naturally generated via brain activity. The brains of children with ASD showed less communication between areas that are important for social information processing compared to the brains of neurotypical children. The amount of communication between these areas was associated with social and social communication difficulties.